The association between reported and calculated reservation wages - René Böheim (University of Essex, Institute for Social and Economic Research (ISER), 2002)
Do reported reservation wages correspond to the concept of reservation wages that economists have? Using panel data on British unemployed I calculate reservation wages from a search model and compare these with reported reservation wages. It is shown that mens reported reservation wages are greater than what the model predicts, and that for women there is hardly a relation between the two variables.
Keywords: 330